COVID-19: an opportunity to re-evaluate the implementation of a One Health approach to tackling emerging infections in Nigeria and other sub-Saharan African countries - Olaniyi Ayobami; Godwin Mark; Zaharat Kadri-Alabi; Chioma Rita Achi; Joy Chinwendu Jacob (SpringerOpen, 2021)
Abstract Background One Health (OH) has resurfaced in the light of the ravaging COVID-19 pandemic. It has been accepted by many local and global health authorities as a suitable approach for preventing and responding to infectious disease outbreaks including pandemics. Main body One Health (OH) is a multisectoral and interdisciplinary framework for managing the animal, human, and ecosystem determinants of health. Globally, the majority of emerging infections in humans including SARS-Cov2-the causative agent of COVID-19-are transmitted from animals through environmental contacts in the last few decades. Yet, even when the biological and social interactions at the human, animal, and environmental interface that drive spillover of zoonotic diseases have been proven, OH strategies to address associated complex health challenges today are still rudimentary in many national health systems. Despite the disproportionate burden of infectious diseases in sub-Saharan Africa, OH is minimally incorporated into routine disease control and national health security programs. Challenges include poor policy support for OH in sub-Saharan Africa, and where some form of policy framework does exist, there are significant implementation bottlenecks. In this paper, we identified ideological, technical, operational, and economic barriers to OH implementation in Nigeria and sub-Saharan Africa, and highlighted possible recommendations across these domains. In order to yield sustainable benefits, a relevant OH policy approach in the sub-Saharan African health systems must derive from a buy-in of the critical mass of stakeholders in the society. Conclusion The implementation of sustainable OH approaches as a countermeasure to recurring emerging infections is a developmental priority for sub-Saharan African countries. A deep understanding of the local context must be leveraged to develop integrative OH solutions that are bold, rooted in science, and proven to be compatible with the level of development in sub-Saharan Africa.